2007
DOI: 10.3892/or.17.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of the cultured human normal biliary tract epithelial cells induced by hepatitis C virus core protein

Abstract: High level expression of hepatitis C virus core protein (HCV-C) was detected in hilar cholangiocarcinoma tissues in our previous studies. This protein played an important role in the process of cancer cell inversion and proliferation, by some direct and indirect effects on certain genes. Based on this observation, we investigated the effect of HCV-C on human normal biliary epithelial (hBE) cell transformation and tumor development. Plasmid pHCV-C encoding the gene of HCV core protein was constructed and transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Core protein interacts with numerous enzymatic systems of the hepatocyte chiefly through activation or repression of proteins such as p53, p21, other transcriptional factors, proto-oncogenes, growth factors, and elements of apoptosis [Kasprzak and Adamek, 2008]. Core protein also facilitates malignant transformation [Shan et al, 2005;Chen et al, 2007], likely through its influence on transcription factor regulation and/or signaling events important for the neoplastic phenotype [Ray and Ray, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Core protein interacts with numerous enzymatic systems of the hepatocyte chiefly through activation or repression of proteins such as p53, p21, other transcriptional factors, proto-oncogenes, growth factors, and elements of apoptosis [Kasprzak and Adamek, 2008]. Core protein also facilitates malignant transformation [Shan et al, 2005;Chen et al, 2007], likely through its influence on transcription factor regulation and/or signaling events important for the neoplastic phenotype [Ray and Ray, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of hilar cholangiocarcinoma grows higher worldwide and the number of hilar cholangiocarcinoma patients with hepatitis C virus (HCV) infection is continuously increasing [1,2]. The core protein of HCV (HCVc) is a structural protein encoded by the most conservative region of HCV genome, and is considered to play an important role in tumor genesis [3,4]. In our previous research, we found that the transfection of HCVc into normal human biliary epithelial cell line led to the malignant transformation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Damage to the bile duct is a histological characteristic of chronic HCV infection, which has been found to be a risk factor for intrahepatic cholangiocarcinoma 16 . The HCV core protein could also promote the malignant transformation of human biliary epithelial cells 17 . Loriot et al .…”
Section: Discussionmentioning
confidence: 99%